Intelligent attitude analysis algorithm based on computer somatosensory technology - Ping, C. (2022 6th International Conference on Electronics, Communication and Aerospace Technology, 2023)
The system captures live images in real time through cameras and superimposes 2D pictures or 3D models of clothing on the images of table tennis players combined with somatosensory detection devices, to realize the fusion of virtual clothing and athletes' postures, and successfully obtain depth images through the Unity3D virtual reality platform. Data and bone and iliac tracking data and preprocessed the data to obtain a method of customizing user poses in Unity3D combined with Kinect somatosensory devices. Develop a set of independent property rights, easy to operate, stable performance, and can be used directly the "Intelligent Table Tennis Special Technical and Tactical Video Analysis System" that is practiced in table tennis and can be put into the market.